Peningkatan Kreativitas Anak Melalui Permainan Finger Painting Tempera di Paud Tadika Puri Kepahiang - Venny Della Amilia; Lina Tri Astuty Sembiring; Dwi Nomi Purati (Journal Of Dehasen Educational Review, 2021)
This study aims: To determine the effect of increasing Children's Mo tor Creativity t hrough the ap plication of f inger p ainting activities in PAUD Group B Tadika Puri. The results of the study showed that the increase in children's innovation from the pre-action stage to my cycle increased every meeting. In the assessment during the action, the number of children who had not developed was 12 people and at the first cycle meeting there were not 2 children who had not developed. Overall children's creativity increases. the average percentage of 33.44% increased to 40% with the criteria starting to develop. Furthermore, there was an increase in the secon d cycle of the first meeting to 61.56% with growth as expected and increased again in the sec ond cycle of the sec ond me eting to 80.3% with the criteria for developing very well. Problems that cause children's creativity to not develop due to several factors such as some children telling stories with friends, children are still afraid to hold cats, used is still lacking, there are still many children who need help and guidance from the teacher, children are not familiar with the media used (finger painting).